Environmental effects on the shape variation of male ultraviolet patterns in the Brimstone butterfly (Gonepteryx rhamni, Pieridae, Lepidoptera) - Pecháček, Pavel; Stella, David; Keil, Petr; Kleisner, Karel (Die Naturwissenschaften, 2014)
The males of the Brimstone butterfly (Gonepteryx rhamni) have ultraviolet pattern on the dorsal surfaces of their wings. Using geometric morphometrics, we have analysed correlations between environmental variables (climate, productivity) and shape variability of the ultraviolet pattern and the forewing in 110 male specimens of G. rhamni collected in the Palaearctic zone. To start with, we subjected the environmental variables to principal component analysis (PCA). The first PCA axis (precipitation, temperature, latitude) significantly correlated with shape variation of the ultraviolet patterns across the Palaearctic. Additionally, we have performed two-block partial least squares (PLS) analysis to assess co-variation between intraspecific shape variation and the variation of 11 environmental variables. The first PLS axis explained 93% of variability and represented the effect of precipitation, temperature and latitude. Along this axis, we observed a systematic increase in the relative area of ultraviolet colouration with increasing temperature and precipitation and decreasing latitude. We conclude that the shape variation of ultraviolet patterns on the forewings of male Brimstones is correlated with large-scale environmental factors.
Keywords: motýli; Pigmentation; Animals; Ultraviolet Rays; životní prostředí; ultrafialové záření; Environment; Wings, Animal; Male; křídla zvířecí; mužské pohlaví; pigmentace; Butterflies; zvířata